2020
DOI: 10.1111/plb.13201
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factors of tall fescue in response to temperature stress

Abstract: Tall fescue (Festuca arundinacea) is an important grass species worldwide, but temperature stress severely affects its distribution and yield. Transcription factors (TFs), as the master switches in sophisticated regulatory networks, play essential roles in plant growth development and abiotic stress responses.• In this study, the comparative transcriptome analysis was performed to explore the commonalities and differences in the response of TFs to the heat (40°C), cold (10°C) and control (22°C) conditions.• A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The WRKY family is a key component of pathways, such as carbohydrate synthesis, senescence, development, and secondary metabolites synthesis and also of the plant-pathogen interaction pathway [89]. Herein, despite being mainly downregulated under increased exposure to DT stress, confirming the negative effect of temperature stress on WRKY genes expression as an energy maintenance mechanism [88], they were also present under stress-free conditions in Pvgstu3-3.4 plants, which could be related to the biotic induced nature of the Pvgstu3-3.4 gene. Other stressrelated TFs were among the top 15 TF families expressed under DT stress in Pvgstu3-3.4, such as the FAR-RED-IMPAIRED RESPONSE1 (FAR1), MADS, Trihelix, ARF, ARR-B, SBP, bZIP and Sigma70-like.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The WRKY family is a key component of pathways, such as carbohydrate synthesis, senescence, development, and secondary metabolites synthesis and also of the plant-pathogen interaction pathway [89]. Herein, despite being mainly downregulated under increased exposure to DT stress, confirming the negative effect of temperature stress on WRKY genes expression as an energy maintenance mechanism [88], they were also present under stress-free conditions in Pvgstu3-3.4 plants, which could be related to the biotic induced nature of the Pvgstu3-3.4 gene. Other stressrelated TFs were among the top 15 TF families expressed under DT stress in Pvgstu3-3.4, such as the FAR-RED-IMPAIRED RESPONSE1 (FAR1), MADS, Trihelix, ARF, ARR-B, SBP, bZIP and Sigma70-like.…”
Section: Discussionmentioning
confidence: 63%
“…NAC TFs are also involved in both abiotic and biotic stress responses [78], and herein they were both presents in stress-free conditions and to a greater extent under DT stress. Heat shock transcription factors (HSF) exert a central regulatory role in alleviating the negative effects of not only high temperature [87,88] but also drought and salt stress [87]. The WRKY family is a key component of pathways, such as carbohydrate synthesis, senescence, development, and secondary metabolites synthesis and also of the plant-pathogen interaction pathway [89].…”
Section: Discussionmentioning
confidence: 99%
“…TFs are proteins that bind DNA in a sequence-specific manner and regulate transcription by acting as recruitment required for RNA polymerase during transcription initiation [ 16 , 48 ]. In plants, TFs can improve disease and stress resistance, mediate growth and development, affect intercellular signaling, regulate the synthesis and accumulation of secondary metabolites, as well as influence plant evolution [ 10 , 16 , 49 , 50 ]. Several studies have demonstrated that the MYB-bHLH-WD40 complex in plants can regulate the biosynthesis of flavonoids, changing the types and contents of metabolites [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, identification and evaluation of TF genes related to stress tolerance are essential for understanding the mechanism of cold tolerance in cucumbers. Previous studies have reported that WRKY TFs are involved in cold tolerance in many plants, such as banana fruits, Coffea canephora , Solanum lycopersicum , Camellia sinensis, and tall fescue [ 43 , 44 , 45 , 46 , 47 ]. In addition, MYB, b-ZIP, Dof, NAC, and HD-ZIP were also reported in plant response to LT, such as the BoPAP1 , an orthologous gene of BoMYB1 , was induced by LT and subsequently activated a subset of anthocyanin structural genes [ 26 ], NAC, MYB, b-ZIP have been reported in response to LT stress in tall fescue [ 45 ], HD-ZIP has been shown playing an important role in mediating the resistance to various abiotic stresses [ 27 ], and Dof is up-regulated in response to cold stress in grapevine [ 48 ].…”
Section: Discussionmentioning
confidence: 99%